Pengaruh efikasi diri, pengetahuan kewirausahaan dan motivasi berprestasi terhadap minat berwirausaha sebagai mediasi pada siswa Kelas X IPS SMA Negeri 1 Driyorejo - Nabilah, Aisyah; Yonisa Kurniawan, Riza (Jurnal Paradigma Ekonomika, 2022)
This study aims to test the entrepreneurial readiness model by presenting the achievement motivation variable as an intervening variable that mediates the relationship between self-efficacy, entrepreneurial knowledge in class x social studies students at SMA Negeri 1 Driyorejo. Collecting data by using a questionnaire. By using proportional random sampling obtained 71 samples, statistical analysis was carried out using Structural Equation Modeling (SEM). The results showed: (1) self-efficacy affects achievement motivation, (2) self-efficacy affects entrepreneurial interest, (3) entrepreneurial knowledge affects achievement motivation, (4) entrepreneurial knowledge affects entrepreneurial interest, (5) achievement motivation does not can mediate the influence of interest in entrepreneurs.